Effectiveness of Media-Based Health Education on Stunting Prevention in Adolescents: A Systematic Review - Marlinawati, Dwi Ayu; Rahfiludin, Mohammad Zen; Mustofa, Syamsulhuda Budi (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2023)
Efforts to promote stunting prevention from an early age can be carried out by media that is effective at targeting youth, where youth activities cannot be separated from the digital world. This systematic review uses a scoping review approach and aims to identify media as an intervention in efforts to prevent stunting in adolescents. Article searches were conducted through Google Scholar, ScienceDirect, and PubMed published in 2018 to 2022 with criteria of full text, open access and keywords such as ‘media AND prevention AND stunting AND effective AND teen’ found 16,508 articles which were then obtained based on the inclusion criteria 8 selected papers. This research describes 5 media interventions for adolescent stunting prevention, including audiovisual; Android applications, social media, leaflets, and booklets. Social media is the most influential media in preventing stunting in adolescents with an increase in the pre-test and post-test difference by TikTok (36.75%), Instagram (22.29%), Twitter (20.25%), Youtube (16.66%), and Facebook (12.61%). Audiovisual videos accompanied by explanations are the second medium that is effectively used, marked by an increase in knowledge from 50.9% to 76.6% compared to the use of videos without reasons. The media interventions have proven effective in increasing adolescents understanding of stunting prevention. Information dissemination to the public, especially youth, is expected to utilize digital media to increase adolescents’ knowledge of stunting prevention which is more effective and efficient.